PENGARUH AROMA UMPAN DAN WARNA KERTAS PERANGKAP TERHADAP JUMLAH LALAT YANG TERPERANGKAP - Sayono ,-; Sifak Mardhotillah; Martini ,- (JURNAL LITBANG, 2005)
Flies constitute mechanical vector of several kinds of diseases. They have fast capability to reproduce. The flies is closely related with the human activities so that they can easily transmit the disease. The activities of flies are influenced mainly by important factors i.e., food, breeding places, light, temperature, humidity, color and texture of places surface. The research is intended to analyze the influence of bait smell and color of paper trap to the number of trapped flies. The experimental research with the design of 4 x 4 factorial implements four kinds of bait smell (frambozen, durian, mango, pineapple) and four color of paper trap (white, yellow, green, and blue). The results show that the average number of trapped Jlies in the white paper trap is 6.33 flies, yellow 5.33 flies, green and blue 2,67 flies, while based on the bait smell it is found that the durian traps 6.33 flies, mango 6.00 flies, frambozen and pineapple 4.33 flies. The statistical results show significant difference between the average number of trapped flies based on color (p=0.000). However the interaction between color and smell does not influence the number of trappedflies (p=0.217) Keyword: bait smell, paper trap color, and trap color.